Molecular genetic markers of hypertension risk in pregnant women with antiphospholipid syndrome - Gulchehra A. Ikhtiyarova; Nigora K. Dustova; Shakhnoza U. Bakhramova; Nodira Kh. Ruzieva; Dilmurod S. Irgashev; Gulnora D. Matrizayeva (Клинический разбор в общей медицине)
Aim. To study the genetic significance of antiphospholipid syndrome in the development of gestational hypertension and the prevention of thrombolytic complications. Study design: an open independent prospective study. Material and methods. 126 women were included in the study: of them, group I (main) consisted of 49 pregnant women with gestational hypertension who had autoantibodies to phospholipids, group II (comparative) 47 women with gestational hypertension in whom autoantibodies to phospholipids were not detected, and group III (control) 30 relatively conditionally healthy pregnant women. Results. Analysis of the data obtained shows that all polymorphisms of the G/A genotype of the F2 gene occur in women with gestational hypertension and in the control group. The study of the genetic structure of this marker indicates that the mutation capacity of the gene is relatively high. in the group of women with gestational hypertension diagnosed with AFS compared to the control group. Allele A and heterozygous type G/A of the genotype of the F2 gene may be one of the important molecular genetic markers of the development of AFS in the population of Uzbekistan (R<0.01). The data obtained showed that the unfavorable allele A of the F2 gene (endocrinopathy) is more common, indicating the presence of autoimmune processes in the body, this position is confirmed by literature data, and in the prevention of AFS, the identification of risk factors in women with gestational hypertension is observed. Conclusion. Rational consideration of these factors determines the direction of preventive measures in women at risk in order to improve the course of pregnancy, childbirth and reproductive outcomes.